Organization of business travel in Russia - E. D. Zotov (Вестник университета)
The article considers the basic concepts of the system of business tourism in Russia and analyses the directions of its organization. The paper lists the economic and socio-cultural factors influencing the behavior of business travelers in Russia. The author formulates recommendations for the main directions of business tourism, taking into account the factors of the external and internal environment that affect the behavior of a business traveler. The study formulates the requirements of the host party for business travelers and companies organizing business tours. The article determines the factors and conditions of accommodation of business travelers in hotels and places of temporary accommodation. The paper describes the ways of holding incentive events for business travelers in the venues of exhibitions, congresses and business meetings.